Hydrophobic chirality amplification in confined water cages - Choong Eui Song (Nature Portfolio, 2019)
Confined environments may have a significant influence on the transition state and, consequently, on the stereochemical outcome of a chemical reaction. Here, the authors show a droplet size-dependent chirality amplification effect for two model reactions in confined organic droplets surrounded by water cages.